Bacteroides pectinophilus sp. nov. and Bacteroides galacturonicus sp. nov.: two pectinolytic bacteria from the human intestinal tract. - Jensen, N S (1986)
Studies on the physiological characteristics of two obligately anaerobic, rod-shaped bacteria from the human intestinal tract indicated that the organisms represented two previously undescribed species of Bacteroides, for which we propose the names Bacteroides pectinophilus (type strain, N3) and Bacteroides galacturonicus (type strain, N6). Both strains were pectinophilic; that is, they utilized as fermentable substrates for growth only pectin and a few related compounds. The two species differed significantly from each other in guanine plus cytosine content of the DNA, in substrate utilization patterns, and in other phenotypic characteristics. Both species deesterified pectin by means of an extracellular pectinesterase (EC 3.1.1.11) activity. Polygalacturonate (the main component of deesterified pectin) was depolymerized extracellularly with formation of unsaturated products by both species. The depolymerizing activity required Ca2+, functioned at a higher rate when polygalacturonate was the substrate as compared with pectin, and had an alkaline pH optimum. These data, as well as viscosity decrease studies and identification of products formed from polygalacturonate, indicated that the extracellular depolymerizing activity of either species was characteristic of an exopectate (exopolygalacturonate) lyase. The exopectate lyase activity had an unusual action pattern that resulted in terminal cleavage of unsaturated trigalacturonic acid units from polygalacturonate. An unsaturated trimer was the major product that accumulated in cell-free reaction mixtures, where it was not cleaved further. Growing cells of both Bacteroides species released the exopectate lyase into the external environment by processes that did not involve cell lysis to any significant extent.(ABSTRACT TRUNCATED AT 250 WORDS)